Aerosol Therapy in Asthma–Why We Are Failing Our Patients and How We Can Do Better - Morton, Robert W.; Elphick, Heather E.; Craven, Vanessa; Shields, Michael D.; Kennedy, Lesley (Frontiers in Pediatrics, 2020)
In order for inhaled corticosteroids to be delivered adequately to the airways they require patients to take them regularly using an effective technique. Patients often have a poor inhaler technique, and this has been shown to result in sub-optimal asthma control. It is important for all clinicians prescribing inhaled medication to be experienced in the correct technique, and take time to train children so that they have mastered corrected inhaler technique. Using Teach to Goal or teach back methodology is a simple and effective way to provide this in the clinic setting. More than one training session is typically needed before children can master correct inhaler technique. Adherence to inhaled therapy has been shown to be sub-optimal in paediatric populations, with studies showing an average rate of around 50%. Subjective methods of measuring adherence have been shown to be inaccurate and overestimate rates. The advent of new technology has allowed adherence rates to be measured electronically, and it has been shown that regular feedback of these data can be effective at improving asthma control. New mobile apps and smart technology aim to engage patients and families with their asthma care. Effective use of these apps in collaboration with health care professionals has a vast potential to improve adherence rates and inhaler technique, resulting in improved asthma control.